(untitled) (Global Conference on Medical and Health Sciences, 2026)
The rapid growth of digital technologies has significantly transformed healthcare systems worldwide. This paper examines the role and impact of modern information technologies in improving healthcare delivery, patient management, and clinical outcomes. It explores key innovations such as electronic health records, telemedicine, artificial intelligence, and mobile health applications. The study also discusses the advantages and challenges associated with the implementation of these technologies. The findings indicate that digital transformation enhances efficiency, accessibility, and quality of healthcare services while raising important concerns related to data security and cost. The paper concludes that continuous technological development is essential for the future of global healthcare.